In vivo response to an implanted shape memory polyurethane foam in a porcine aneurysm model. Issue 5 (23rd May 2013) - Rodriguez, Jennifer N.; Clubb, Fred J.; Wilson, Thomas S.; Miller, Matthew W.; Fossum, Theresa W.; Hartman, Jonathan; Tuzun, Egemen; Singhal, Pooja; Maitland, Duncan J.
Abstract Cerebral aneurysms treated by traditional endovascular methods using platinum coils have a tendency to be unstable, either due to chronic inflammation, compaction of coils, or growth of the aneurysm. We propose to use alternate filling methods for the treatment of intracranial aneurysms using polyurethane‐based shape memory polymer (SMP) foams. SMP polyurethane foams were surgically implanted in a porcine aneurysm model to determine biocompatibility, localized thrombogenicity, and their ability to serve as a stable filler material within an aneurysm. The degree of healing was evaluated via gross observation, histopathology, and low vacuum scanning electron microscopy imaging after 0, 30, and 90 days. Clotting was initiated within the SMP foam at time 0 (<1 h exposure to blood before euthanization), partial healing was observed at 30 days, and almost complete healing had occurred at 90 days in vivo, with minimal inflammatory response. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1231–1242, 2014.